Experimental Study of Polyester Mooring Lines - Nur Aireen bt. Amran; Jaswar Koto; C.L. Siow (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2017)
Mooring lines have several types of material which is chain, wire, synthetic fiber rope and hybrid. Mostly, in oil and gas industry is use chain and wire rope as a mooring line for shallow water platform. When exploitation of oil and gas become deep, synthetic fiber is use as an alternative for mooring line. This paper focused discussion on experimental of hybrid mooring lines for deep water mooring line. The tensile tests have been done for preliminary design stage. The test is to identify the material properties of mooring line. At this stage only focus on the steel wire rope with length 200mm and nominal diameter 3mm, 4mm, 5mm and 6mm. Finally, the conclusion and important summaries were presented according to the data collected.